Community Participation Aspects in Supporting Cibodas Village towards Eco-village - Ratnaningsih Ratnaningsih; Dwi Indrawati; Etty Indrawati; Lailatus Siami (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2020)
The Cibodas village community, Pasirjambu Sub-District, Bandung Regency has majority occupation as farmer and livestock, especially in dairy cattle. The main problem faced by them, is livestock waste and garbage not being managed properly, many people who do not have permanent jobs, cattle farms, experiencing a decrease in quality and quantity due to the difficulty of fodder and high cost of concentrated feed. The purpose of this activity is to offer a solution to increase employment opportunities by encouraging integrated agriculture and livestock businesses to be environmentally friendly and waste treatment to become economically valuable materials. The Method to achieve community participation was conducted through the following step, a) Village community meeting (rembug desa), b) Focus Group Discussion 1 and 2 c) Training for the facilitator. And the method to support the achievement of ecovillage were established pilot facilities and job opportunities such as agriculture waste treatment, agroforestry, and Integrated municipal waste treatment facilities.  The result of the activity has shown by an active role, joining of several community leaders, and has established youth groups as the next generation in agricultural, and livestock business, municipal waste management efforts. By processing waste into fertilizer, biogas, and fodder, the farming business has become low-cost and environmentally friendly. The utilization of organic waste by Black soldier fly is an additional income for garbage managers in the Injeman Garbage Treatment Unit. It is concluded that the involvement of community leaders and youth group as a facilitator, in the activities indicate the effort of Cibodas towards Eco-village will run sustainably.